1992
DOI: 10.1021/j100193a060
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cyclohexadiene with platinum(111) studied by BPTDS and HREELS

Abstract: The interactions of 1,3-and l,4-cyclohexadiene with Pt(ll1) have been studied with bismuth postdosing thermal desorption mass spectroscopy (BPTDS) and high-resolution electron energy loss spectroscopy (HREELS). Both species adsorb molecularly on Pt( 11 1) at 100 K. Upon warming, both species dehydrogenate completely to produce adsorbed benzene. The reaction occurs at about 230-260 K with an activation energy of 14 f 2 kcalfmol. The adsorbed benzene thus produced either dehydrogenates, ultimately to graphitic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
75
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(100 citation statements)
references
References 4 publications
23
75
2
Order By: Relevance
“…Since adsorbed benzene remains molecular in our experimental conditions, and since the periodicities are very similar to those of the structure formed by 1,3-cyclohexadiene, we conclude that this molecule dehydrogenates to benzene. This agrees with the conclusions of a thermal desorption mass spectroscopy study performed by the Campbell group [24], which showed that at low coverage 1,3-cyclohexadiene dehydrogenates to benzene at temperatures between 20 K and 30 K lower than that for the dehydrogenation of 1,4-cyclohexadiene. Bismuth post dosing thermal desorption indicates dehydrogenation temperatures of $230 K and 260 K respectively while thermal desorption spectroscopy shows H 2 evolution beginning at $280 K and 300 K. Our studies indicate temperatures higher than 230 K and 260 K. We attribute this to the fact that in our case we are close to saturation coverage, where fewer vacant sites needed for hydrogen abstraction exist.…”
Section: Resultssupporting
confidence: 91%
“…Since adsorbed benzene remains molecular in our experimental conditions, and since the periodicities are very similar to those of the structure formed by 1,3-cyclohexadiene, we conclude that this molecule dehydrogenates to benzene. This agrees with the conclusions of a thermal desorption mass spectroscopy study performed by the Campbell group [24], which showed that at low coverage 1,3-cyclohexadiene dehydrogenates to benzene at temperatures between 20 K and 30 K lower than that for the dehydrogenation of 1,4-cyclohexadiene. Bismuth post dosing thermal desorption indicates dehydrogenation temperatures of $230 K and 260 K respectively while thermal desorption spectroscopy shows H 2 evolution beginning at $280 K and 300 K. Our studies indicate temperatures higher than 230 K and 260 K. We attribute this to the fact that in our case we are close to saturation coverage, where fewer vacant sites needed for hydrogen abstraction exist.…”
Section: Resultssupporting
confidence: 91%
“…TPD has been used to assess the adsorption energy of 1,4-cyclohexadiene (e.g. [10,12]). However, no value could be determined as 1,4-cyclohexadiene dehydrogenates rather than desorbs.…”
Section: Adsorption Of 14-cyclohexadienementioning
confidence: 99%
“…The adsorption and dehydrogenation of 1,3-cyclohexadiene on Pt(1 1 1) has been investigated by different surface science techniques [9][10][11][12][13]. No experimentally determined adsorption energy is available, since the dehydrogenation barrier is lower than the desorption energy.…”
Section: Adsorption Of 13-cyclohexadienementioning
confidence: 99%
See 1 more Smart Citation
“…For the first C-H scission, the calculated energetic values are E a,1 = 1.65 eV and E r,1 = 0.50 eV. In experiments, the barrier for benzene dehydrogenation is found to be 1.21 to 1.87 eV [102,116,117]. On a cluster model, E r for the dehydrogenation of hollow-bound benzene is endothermic by 0.52 eV [67].…”
Section: Benzene Dehydrogenationmentioning
confidence: 92%